MODEL KAUSALITAS DAN GUNCANGAN BELANJA PEMERINTAH TERHADAP PRODUK DOMESTIK BRUTO DI INDONESIA - Edy Sutriono (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2018)
This research was conducted in the first semester of 2018 aimed at determining whether there is a causal and respond relationship between government spending and GDP using data from 2005 to 2017. The method used is Granger Causality and Vector Autoregression. The results of the study state that employee spending, goods expenditure, economic and tourism functions and culture influence reciprocal GDP, while capital expenditure, social assistance, education and health functions only influence GDP. Employee spending shocks, social assistance, health functions have no significant effect and are responded to by GDP, while shocks to goods, capital, economic, education, tourism and cultural spending are very influential and are responded to by GDP. The implication for the government is in compiling the next fiscal measures and policies in allocating expenditure in the APBN to increase the role of government spending to be able to increase gross domestic product and the national economy. For the general public, as the mandate of the State Budget, it can better know the direction and impact of the State Budget on the economy.